Diplomatic discourse in cross-cultural dimension - Agnur, Khalel; Mamedova, Fatima; Dulaeva, Elnara (Opción)
From the values, ideas and beliefs that are hidden in the political goals to the characteristic patterns of how a nation communicates with publics everything is reflected with cultural tones. Facing the challenges of 21st century, the issue of intersection between diplomatic processes and cultural discourse becomes very relevant. This article explores the interrelation of culture and diplomacy, paying attention to where their paths meet and what can be learned while pausing at those “meeting points”. The idea is to ignite thinking on culture and create a cultural awakening in diplomacy. The article tries to increase awareness on urgency that this topic will gain in the near future.